Realizing the Ideal Model of Digital Islamic Boarding Schools: a Systematic Literature Review Analysis - Ahmad Fauzi; Muhamad Arif; Ali Mustofa (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
To analyze the transformation of Islamic boarding schools (Pesantren) in the digital era, assess the contribution of digital technology to Islamic boarding schools, and propose the ideal model for digital Islamic boarding schools. The study uses a systematic literature review method utilizing the "Publish or Perish" application. Keywords such as "Pesantren Digital “or” Pesantren Technology “or” Pesantren Virtual “or” Islamic Boarding School Digital “or” Islamic Boarding School Technology “or” and Islamic Boarding School Virtual” were searched in the global indexing database "Scopus," followed by PRISMA data analysis. The digital transformation model in Islamic boarding schools includes changes in management, administration, learning, and digital skill development for students. The contribution of digital technology is diverse, ranging from improving administration and management, increasing access to digital-based learning, strengthening interactions between Islamic boarding schools, alumni, and the community, developing student skills in utilizing digital tools, and facilitating the spread of Islamic preaching (rahmatan lil alamin). This study implies that integrating digital technologies into Islamic boarding schools offers significant opportunities to improve educational practices and administrative efficiency. This study provides a new perspective on the ideal model of digital Islamic boarding schools using Giddens' perspective of Giddens' four elements.